Investigating failure to implement contactless payments: a case of Near Field Communication payment systems in South Africa - Muchinguri, Cosmas (Department of Information Systems, 2017)
Near Field Communication (NFC) contactless payment systems are being touted as the future for retail payments and public transport fare-collection systems. Studies have shown that such initiatives require many organisations from different industries to work together for the goal to be realised. The effort and collaboration required to achieve this goal cannot be underestimated. The aim of this research is to explore the failure of NFC contactless payment system implementations. The Actor Network Theory (ANT) has been shown as appropriate for investigating IT implementation failures, and so serves as a study lens for this investigation. A case study research strategy was used in the research to gain an understanding of the as-lived experiences of the actors involved in an NFC payment system implementation. The data was collected using different methods such as interviews and review of project documents. Thematic analysis techniques were used to trace and unpack the interactions occurring around implementation of these NFC payment systems and the challenges encountered. The key factors identified as leading to the NFC payment system implementation failure are external dependencies, lack of required financial investments, interoperability issues due to new and legacy systems, and lack of clear governance structures and bodies. The results of the study suggest that, when there is external dependence, but the tasks, resources required, actors' capabilities, workloads and the duration for completing these tasks are not known, then there will be frequent conflicts, leading to NFC payment system implementation failure. Regulatory bodies and clear leadership structures in collaborative NFC payment system implementation were found to be crucial. The results of the study also propose that when new and legacy systems from multiple actors are to be integrated to develop an NFC payment platform, there is likely going to be system interoperability issues due to the numerous vendors involved, which lead to failure. In addition, unwillingness to commit to the required capital investments by stakeholders was identified as leading to the failure of the NFC payment system implementation. A prescriptive framework is developed based on these lessons that could aid in ensuring better outcomes in future NFC payment systems implementations.